Resource-based theory and mergers & acquisitions success - Plina Grill; Rudi K. F. Bresser (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
Mergers & acquisitions (M&A) are most popular external growth strategies. While the number of M&A has been increasing during the past decades, on average, only the shareholders of target firms gain value during the acquisitions process, while acquirers do not receive abnormal positive returns. This paper analyses the impact of strategically valuable resources on the success of M&A decisions. We test complementary resource-based hypotheses regarding the value of M&A for the shareholders of both transaction partners. Our sample consists of transactions in the pharmaceutical and biotechnological industry. The results of our study show that the shareholders of both transaction partners will gain above average positive returns only when the acquirer and the target own and combine strategically valuable resources and capabilities.
Keywords: 650